Adoption of Building Information Modelling technology (BIM): Perspectives from Malaysian engineering consulting services firms - Rogers, J.; Chong, Heap Yih; Preece, C. (Emerald Group Publishing Ltd., 2015)
Purpose: Building Information Modelling (BIM) technology has been well received by the Malaysian construction industry, yet the adoption rate is extremely slow. Many areas of adoption issues and know how regarding BM were investigated. However, no prior research has considered the perspective from engineering consulting services (ECS) firms. Therefore, the purpose of this paper is to explore the overview and adoption of BM from the perspective of Malaysian ECS firms, with its objectives first, to determine the perceptions, barriers, governmental support and intentions in adopting BM, and second, to identify the key drivers for adopting BM within two years. Design/methodology/approach: The primary data were collected from focus group interview and questionnaire survey to achieve the first objective, and subsequently, the second objective was achieved based on Pearson relationship analysis. Findings: The results show that the firms have a concept of BM that equates to industry authorities' norms; yet the lack of well-trained personnel, guidance and governmental supports were identified as the main barriers to adoption. Nevertheless, the firms were prepared to adopt BM where market demands and competitive advantage were the main drivers to adoption within two years. Originality/value: A different perspective has been highlighted in adoption of BM. It renders a new insight into the effective adoption and use of BM from the ECS firms' perspective.